2017
DOI: 10.1109/tbme.2016.2633391
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Detection and Classification of High-Frequency Oscillations in Depth-EEG Signals

Abstract: Experimental results show the feasibility of a robust and universal detector.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
56
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(56 citation statements)
references
References 29 publications
0
56
0
Order By: Relevance
“…Therefore, they confirmed that HFO classification is a multiclass problem. Subsequently, different classification methods have been tested: LDA [19], support vector machine (SVM) [13,20,21], and decision tree [22], combined with different feature sets.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, they confirmed that HFO classification is a multiclass problem. Subsequently, different classification methods have been tested: LDA [19], support vector machine (SVM) [13,20,21], and decision tree [22], combined with different feature sets.…”
Section: Introductionmentioning
confidence: 99%
“…However, FDRs computed on real iEEGs were higher than FDRs computed on simulated data. This clearly reflected that iEEG signals were highly contaminated with artefacts and revealed the need of classifying the detected events like we did in [17].…”
Section: B Results and Discussionmentioning
confidence: 51%
“…The Gabor atoms were chosen optimally regarding the time-frequency uncertainly principle (see [9] and our previous works [17,18] for more details). Gabor function is defined as a Gaussian envelope modulated by complex sinusoids:…”
Section: B Hfos Detection Methodsmentioning
confidence: 99%
“…However, HFOs-related studies to identify the possible seizure onset channels need the long-time iEEG data to calculate the baseline. Jrad et al proposed automatic HFO detection with multi-class SVM in depth-EEG signals 59 . In their study, the performance evaluation matrices for evaluating the system were used in terms of sensitivity and false discovery rate (FDR).…”
Section: Discussionmentioning
confidence: 99%
“…The combination of short-time energy (STE) and CNN also used in recent study for identifying HFOs 62 . In their study, the performance of the system in terms of sensitivity and FDR are used to evaluate their system and compared with three related existing studies 32,36,59 . They achieved higher average results with five adult patients for ripple (Sen: 81.1% and FDR: 30.2%) and fast ripple (Sen: 74.6% and FDR: 6.3%).…”
Section: Discussionmentioning
confidence: 99%